Deeply embedded corneal foreign bodies with fungal keratitis secondary to “rambutan” fruit fall - Rosli, Abdul Hadi; Abdurrahman, Muhammad Yusuf; Mohd. Kamal, Khairidzan (Cureus Inc, 2022)
Rambutan is widely found in remote areas in Southeast Asia. It may lead to serious ocular trauma if it accidentally hit the eyes. This case report describes a patient who presented with deeply embedded cornea foreign body and fungal keratitis following direct ocular trauma by rambutan fruit. This report identified the features of this fruit that had the potential to cause serious ocular trauma. Ocular protection equipment is essential to prevent injury during harvesting the fruit.